Nutrient profiling of traditionally sun-dried Acetes - Balange, A. K.; Martin Xavier, K. A.; Kumar, Sanath; Nayak, B. B.; Venkateshwarlu, G.; Shitole, S. S. (Indian Journal of Fisheries, 2018)
An attempt was made to study the nutrient profile of traditionally sun-dried Acetes with respect to its proximate composition, amino acids, fatty acids, minerals and heavy metals. From the results, it was found that dried Acetes contained 19.00±0.70% moisture, 48.29 ± 0.64% crude protein, 16.05±0.52% ash and 3.62±0.09% crude fat. Biopolymer content in dried Acetes showed 10% chitin. Amino acid profile of dried Acetes confirmed that it could serve as a significant source of essential amino acids. Fatty acid profile revealed 9, 12-otadecadieonic acid (17.08%), docosahexaenoic acid (DHA) (15.69%), eicosapentaenoic acid (EPA) (13.45%) and docosanoic acid (11.75%) as the major fatty acids. Mineral profiling indicated the presence of P, Ca, K, Mg, Na and Fe. Heavy metal analysis indicated the presence of Cd, Cu, Pb and Zn. However, harmful metals like cadmium and lead were found to be low. From microbiological quality analysis of dried Acetes, the total plate count and faecal coliforms count were found to be 4.1 x 103 cfu g-1 and 35 MPN per100 ml, respectively while Staphylococcus aureus colonies were not detected. Results of the study indicated that dried Acetes was not processed properly and hygienically as revealed by its content of high moisture and faecal coliforms, respectively. Further, based on proximate composition, amino acids, fatty acids and mineral profile, it can be concluded that dried Acetes can be a good source of health beneficial nutrients.